Treatment of acquired aphasia: speech therapists and volunteers compared. Issue 11 (November 1982) - David, R; Enderby, P; Bainton, D
Abstract : This paper reports on a multicentre trial comparing the effects of speech therapists and untrained volunteers on recovery from aphasia following stroke. One hundred and fifty-five patients entered the study and 96 completed it. Patients in both treatment groups improved, and there were no differences overall in the amount of progress made. A small subgroup of patients who started treatment much later had equivalent initial scores and made almost as much progress as those who started earlier. It is suggested that the improvement in communication which occurred during treatment may be due both to the appropriate stimulation which was based on detailed and accurate speech therapy assessment, and to the regular support and encouragement provided within the therapeutic relationship.